University? No thanks! An empirical study of why German apprentices with the Abitur choose not to go to university - Pilz, Matthias [Verfasser]; Ebner, Christian [Verfasser]; Edeling, Sabrina [Verfasser] (My University, 2020)
"More than a quarter of all trainees in Germany's dual vocational training system have the Abitur - the German school-leaving qualification that entitles them to go to university. Some go to university after completing their apprenticeship, but others move straight into full-time employment. There is currently very little reliable empirical data about the reasons for these decisions, particularly among the latter group. This study considers around 1,100 trainees with the Abitur in four different training occupations in the German federal state of North Rhine-Westphalia, investigating the sociodemographic profile and the motives. It also explores in depth and critically discusses the motives of those not intending to go to university. The findings demonstrate that those choosing not to go to university are neither academically weak nor particularly risk-averse in their assessment of their prospects of obtaining a degree. They are more motivated by having a practical orientation, by financial factors and by good employment prospects." (authors' abstract; BIBB-Doku)
Keywords: P 2.3 Auszubildende; P 2.1.1 Ohne Schulabschluss; L 5 Beratung & Orientierung; Auszubildender; Abiturient; Studienberechtigter; Ausbildungswahl; Berufswahlmotiv; Einflussfaktor; Ausbildungsmotivation